Intrathecal Morphine versus Intrathecal Hydromorphone for Analgesia after Cesarean Delivery: A Randomized Clinical Trial. (June 2020) - Sharpe, Emily E.; Molitor, Rochelle J.; Arendt, Katherine W.; Torbenson, Vanessa E.; Olsen, David A.; Johnson, Rebecca L.; Schroeder, Darrell R.; Jacob, Adam K.; Niesen, Adam D.; Sviggum, Hans P.
Abstract : Background: Intrathecal opioids are routinely administered during spinal anesthesia for postcesarean analgesia. The effectiveness of intrathecal morphine for postcesarean analgesia is well established, and the use of intrathecal hydromorphone is growing. No prospective studies have compared the effectiveness of equipotent doses of intrathecal morphine versus intrathecal hydromorphone as part of a multimodal analgesic regimen for postcesarean analgesia. The authors hypothesized that intrathecal morphine would result in superior analgesia compared with intrathecal hydromorphone 24 h after delivery. Methods: In this single-center, double-blinded, randomized trial, 138 parturients undergoing scheduled cesarean delivery were randomized to receive 150 µg of intrathecal morphine or 75 µg of intrathecal hydromorphone as part of a primary spinal anesthetic and multimodal analgesic regimen; 134 parturients were included in the analysis. The primary outcome was the numerical rating scale score for pain with movement 24 h after delivery. Static and dynamic pain scores, nausea, pruritus, degree of sedation, and patient satisfaction were assessed every 6 h for 36 h postpartum. Total opioid consumption was recorded. Results: There was no significant difference in pain scores with movement at 24 h (intrathecal hydromorphone median [25th, 75th] 4 [3, 5] and intrathecal morphine 3 [2, 4.5]) or at any time point (estimated difference, 0.5; 95% CI, 0 to 1; P = 0.139). Opioid received in the first 24 h did not differ between groups (median [25th, 75th] oral morphine milligram equivalents for intrathecal hydromorphone 30 [7.5, 45.06] vs. intrathecal morphine 22.5 [14.0, 37.5], P = 0.769). From Kaplan–Meier analysis, the median time to first opioid request was 5.4 h for hydromorphone and 12.1 h for morphine (log-rank test P = 0.200). Conclusions: Although the hypothesis was that intrathecal morphine would provide superior analgesia to intrathecal hydromorphone, the results did not confirm this. At the doses studied, both intrathecal morphine and intrathecal hydromorphone provide effective postcesarean analgesia when combined with a multimodal analgesia regimen. Abstract : In a randomized, double-blinded trial, intrathecal hydromorphone and intrathecal morphine were compared in women receiving cesarean delivery using pain score at 24 h as the primary outcome. The analgesia provided by morphine was not superior to that provided by hydromorphone. In addition, breakthrough analgesic requirements were similar for the two groups.